Widening the genetic base of cultivated gene pool following introgression from wild Lens taxa. (27th June 2018) - Singh, Mohar; Sharma, Shyam K.; Singh, Badal; Malhotra, Nikhil; Chandora, Rahul; Sarker, Ashutosh; Singh, Kuldeep; Gupta, Dorin
Abstract: Wild Lens taxa are a reservoir of useful rare genes/alleles for widening the genetic base and synthesis of a new gene pool of lentil. To maximize and sustain lentil production, new gene sources are needed to be identified and incorporated into cultivated background. This needs a comprehensive approach to accumulate favourable alleles from distantly related germplasm for widening of the cultivated gene pool and would be the most appropriate strategy to solve the various problems associated with stressed crop production and plateaued yields. Furthermore, expansion of deeper understanding of lentil genomics along with extensive research undertaken in other crop species can provide suitable guidelines to cover the distribution of Lens genus and component gene pools for further remarkable progress in lentil genetic improvement. This review aims at the genus Lens distribution and gene pools, crop germplasm conserved in ex‐situ and in‐situ collection, wild species characterization and evaluation for useful traits of interest to solve production‐related problems, highlight useful gene sources present in different gene pools and the progress achieved for widening the genetic base of cultivated varieties of lentil through wide hybridization and exploring lentil genomics.